Odiparcil, a potential glycosaminoglycans clearance therapy in mucopolysaccharidosis VI—Evidence from in vitro and in vivo models - Entchev, Eugeni; Jantzen, Ingrid; Masson, Philippe; Bocart, Stephanie; Bournique, Bruno; Luccarini, Jean-Michel; Bouchot, Andre; Lacombe, Olivier; Junien, Jean-Louis; Broqua, Pierre; Tallandier, Mireille (PloS one, 2020)
Mucopolysaccharidoses are a class of lysosomal storage diseases, characterized by enzymatic deficiency in the degradation of specific glycosaminoglycans (GAG). Pathological accumulation of excess GAG leads to multiple clinical symptoms with systemic character, most severely affecting bones, muscles and connective tissues. Current therapies include periodic intravenous infusion of supplementary recombinant enzyme (Enzyme Replacement Therapy-ERT) or bone marrow transplantation. However, ERT has limited efficacy due to poor penetration in some organs and tissues. Here, we investigated the potential of the β-D-xyloside derivative odiparcil as an oral GAG clearance therapy for Maroteaux-Lamy syndrome (Mucopolysaccharidosis type VI, MPS VI). In vitro, in bovine aortic endothelial cells, odiparcil stimulated the secretion of sulphated GAG into culture media, mainly of chondroitin sulphate (CS) /dermatan sulphate (DS) type. Efficacy of odiparcil in reducing intracellular GAG content was investigated in skin fibroblasts from MPS VI patients where odiparcil was shown to reduce efficiently the accumulation of intracellular CS with an EC50 in the range of 1 μM. In vivo, in wild type rats, after oral administrations, odiparcil was well distributed, achieving μM concentrations in MPS VI disease-relevant tissues and organs (bone, cartilage, heart and cornea). In MPS VI Arylsulphatase B deficient mice (Arsb-), after chronic oral administration, odiparcil consistently stimulated the urinary excretion of sulphated GAG throughout the treatment period and significantly reduced tissue GAG accumulation in liver and kidney. Furthermore, odiparcil diminished the pathological cartilage thickening observed in trachea and femoral growth plates of MPS VI mice. The therapeutic efficacy of odiparcil was similar in models of early (treatment starting in juvenile, 4 weeks old mice) or established disease (treatment starting in adult, 3 months old mice). Our data demonstrate that odiparcil effectively diverts the synthesis of cellular glycosaminoglycans into secreted soluble species and this effect can be used for reducing cellular and tissue GAG accumulation in MPS VI models. Therefore, our data reveal the potential of odiparcil as an oral GAG clearance therapy for MPS VI patients.